Impact of ball possession time and number of passes on the efficiency of scoring in men's water polo - Theodoros Platanou; Evdokia Varamenti (Termedia Publishing House, 2022)
Purpose This study aimed to explore whether a meaningful relationship existed between scoring in men's water polo and ball possession time and the number of passes in even and extra player offence conditions. Methods Overall, 24 close matches played during international competitions were analysed twice, for the winning and losing teams separately. This allowed to collect a sample consisting of 1588 offences when teams played in equal conditions and 492 with an extra player. Results For effective scoring in even conditions, the results demonstrated significant relationships between the exchanging of many passes (7.78 ± 1.09 passes) and short-duration attacks lasting for 1-10 s (7.87 ± 2.29 s) ( p = 0.05). In the extra player condition, a considerable relationship was noted between short to average ball possession time and scoring ( p = 0.05). However, the effect size for these differences ranged from moderate to low. Conclusions Knowledge of this study results could help coaches design specific workouts during routine practices and make decisions during matches.